The Impact of Compulsive Ethanol Consumption on Gut and Brain Neurochemicals (P14-003-19). (13th June 2019) - Bauer, Ella; Shoeman, Allyse; Daniels, Karrie; Lyte, Mark; Clark, Peter
Abstract: Objectives: Binge drinking is a significant problem costing the United States 191 billion dollars annually and is also a significant risk factor for many dietary (e.g., diabetes) and neurodegenerative diseases (e.g., Alzheimer's and Parkinson's disease). Interestingly, the gut-brain axis has been implicated in the development of neurodegenerative and dietary-related diseases, thus, may mediate the harmful consequences of alcohol abuse on the brain and body. However, the mechanisms are not well understood. We hypothesize that compulsive ethanol consumption will alter the expression of neurochemicals in the mouse gut in a manner that will be correlated to changes in the expression of brain neurochemicals. Methods: We examined catecholamines and structurally similar metabolites following repeated bouts of "Drinking in the Dark"- a mouse model of compulsive alcohol-seeking during which mice reliably reach blood ethanol concentrations greater than 100 mg/dL. Adult female and male C57BL/6 J mice received access to either 20% ethanol ( n  = 12 male, n  = 12 female) or water ( n  = 12 male, n  = 12 female) for a two-hour period during the dark cycle over three consecutive days. On the fourth day, mice received access to ethanol or water for four hours, and samples of the intestine, intestinal contents, liver, and brain subregions were analyzed for tissue-specific neurochemical concentrations using UHPLC. Results: Ethanol consumption data indicate that binge-drinking female mice consume 36% more ethanol than female water controls and consume 32% more ethanol than binge-drinking male mice on day 4 of the "Drinking in the Dark" protocol. Preliminary neurochemical data indicate compulsive ethanol drinking contributes to trending increases in norepinephrine (17% striatum; 18% hypothalamus) in males whereas females have trending decreases in striatal L-DOPA (15%), 5-HIAA (14%), and 27% more hypothalamic L-DOPA and 5-HIAA when compared with water controls. Conclusions: Binge drinking may contribute to region- and sex-specific neurochemical differences in the brain, thus, further neurochemical analyses on the gut could provide insight into the etiology of neurodegenerative and dietary diseases following alcohol abuse. Funding Sources: Supported from Iowa State University start-up funds.